THE ROLE OF ACTORS NETWORK IN THE REGIONAL COOPERATION: A CASE STUDY OF THE ASEAN MARITIME OUTLOOK - Dhani Akbar; Wayu Eko Yudiatmaja; Firman Firman; Kustiawan Kustiawan; Teguh Setiandika Igiasi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The ASEAN Maritime Outlook (AMO) represents a strategic initiative designed to strengthen maritime cooperation in Southeast Asia; however, its effectiveness largely depends on the dynamics of inter-actor networks involved in its formulation and implementation. This study analyzes the engagement and relationships among various actors—including states, donor agencies, international organizations, research institutions, and civil society—using an actor-network analysis approach and secondary data drawn from official documents, partner institution reports, and academic publications. The findings indicate that ASEAN’s maritime cooperation operates in a multi-level and collaborative manner, with Indonesia, Vietnam, and Singapore playing dominant roles, while non-state actors significantly contribute to the transnational dimension of maritime policy. The results suggest that the effectiveness of ASEAN’s maritime governance is shaped less by formal institutional structures than by the strength of adaptive and inclusive actor coordination, thereby enriching the discourse on contemporary regionalism from the perspectives of political science and international relations.